2016
DOI: 10.1037/cpp0000141
|View full text |Cite
|
Sign up to set email alerts
|

A brief behavioral intervention for insomnia in adolescents with autism spectrum disorders.

Abstract: Behavioral sleep education has shown promise in young children with autism spectrum disorder (ASD), but has received much less study in adolescents with ASD. We conducted a pilot study of a brief sleep intervention delivered to 18 adolescents, ages 11-18 years, and their parents. Adolescents had sleep onset delay, night wakings, or both. Actigraphy and parent and adolescent questionnaires were collected at baseline and 1 month after treatment. Sleep education, delivered in a 2-session format, was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Our findings will need to be confirmed in larger samples. These preliminary findings emphasize that a multifactorial approach, which includes elements focused on behavioral sleep education (Loring et al 2016), an evidence-based approach to improve sleep quality (e.g., avoiding too early of a bedtime, limiting electronic devices, limiting, caffeine intake, increasing exercise, and implementing a calming bedtime routine) is important in treating sleep disturbance in this population.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our findings will need to be confirmed in larger samples. These preliminary findings emphasize that a multifactorial approach, which includes elements focused on behavioral sleep education (Loring et al 2016), an evidence-based approach to improve sleep quality (e.g., avoiding too early of a bedtime, limiting electronic devices, limiting, caffeine intake, increasing exercise, and implementing a calming bedtime routine) is important in treating sleep disturbance in this population.…”
Section: Discussionmentioning
confidence: 82%
“…Tan et al (2012) implemented sleep hygiene interventions which significantly improved the total ASHS scores in an adolescent population with self-reported sleep problems. Loring et al (2016) also reported that ASHS subscales (cognitive, behavioral, sleep stability, and sleep environment) showed statistically significant improvement with behavioral sleep education and sleep hygiene interventions. In both our TD and ASD groups, there were sleep hygiene difficulties resulting in relatively low ASHS scores.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A review of the autism and sleep literature revealed that only one study has actively included adolescents with ASD in the therapeutic process. Loring et al (2016) provided two sleepeducation sessions to 18 adolescents (11 to 18 years old) with high-functioning autism (HFA, IQ >70) and their parents. Session one targeted sleep hygiene including bedtime routine and arranging the sleep environment, and session two taught relaxation and distraction techniques to facilitate sleep onset.…”
mentioning
confidence: 99%
“…Although the correlations are small, these results are in line with previous research about the relationships between autism and reductions in sleep time (Baker and Richdale 2015 ; Salmela et al 2019 ; Veach et al 2017), and day-time functioning impairments (Richdale et al 2014 ). One education-based study (Loring et al 2016 ) using sleep hygiene and cognitive behavioral techniques (CBT-I) with a sample of adolescents with autism and demonstrated significant improvement via actigraphy measurement. Meta-analyses (e.g.…”
Section: Discussionmentioning
confidence: 99%